Experiences of Middle-Level Students, Teachers, and Parents in the Do the Write Thing Violence Prevention Program - Myer, Rick A. (2016)
We examined experiences of participants in Do the Write Thing national violence prevention program for middle-level students. Using mixed methods, we conducted surveys and focus groups with students, parents, and teachers who attended the program’s National Recognition Week in Washington, DC. Results revealed important affective, behavioral, and cognitive impacts on participants, including improved relationships, increased understanding of violence, and commitment to reduce violence. Participants from cities where insufficient time and resources were devoted to the project did not experience significant change. Teachers reported developing greater empathy for their students and making substantial changes in their teaching, providing support for students and infusing activities addressing violence into their curriculum. Recommendations are made for increased program support and future research